Pesta Buah dan Bunga Analisis Kearifan Lokal Dalam Tinjauan Komunikasi Budaya Masyarakat Karo: Karo People's Fruit and Flower Festival - Endah Rananda Gita Br Purba (Journalism, Public Relation and Media Communication Studies Journal (JPRMEDCOM), 2023)
Study the Flower and Fruit Festival of the Kalo Society of Berastagi and explain what the Fruit and Flower Festival looks like, its implementation, development and its impact on the Karo people. The Flower and Fruit Festival was originally held to thank the gods who gave the land of Karo a fertile land. Karo is like a rural community in Indonesia, whose life is based on ritual-influenced agricultural values. Besides showing gratitude, the purpose of this celebration is also to promote the diamond harvest. A fruit and flower festival to attract foreign tourists to the Kaloshimarem area. There was a financial crisis in ancient times, and the flower and fruit festival was suspended for a while. However, Caro's enthusiasm for holding this event led to the Fruit and Flower Festival being held again. These fruits and flowers should always be placed in such a way as to attract the attention of tourists and also continue to carry on the ancient customs and maintain the uniqueness of Burastagi.